The Impact of Wage-Setting Institutions on the Incidence of Public Employment in the OECD: 1960-98 - Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2002)
Using data on 17 OECD countries for 1960-98, this paper studies the impact of unions on public employment incidence, using macrodata and microdata. Macrodata show that greater coverage by centralized collective bargaining institutions raises the public employment share, controlling for country effects and country-specific trends. Microdata show that this effect is more positive for outsiders: women, and younger and older men, suggesting that government is employer of last resort. Greater unionization lowers public sector wage premia, particularly for women, suggesting that some of the public employment results may reflect movements along the labor demand curve rather than conscious policy.
Keywords: H11; J58; 330